Predicted climate change will increase the truffle cultivation potential in central Europe - Čejka, Tomáš; Trnka, Miroslav; Krusic, Paul J; Stobbe, Ulrich; Oliach, Daniel; Václavík, Tomáš; Tegel, Willy; Büntgen, Ulf (Scientific reports, 2020)
Climate change affects the distribution of many species, including Burgundy and Périgord truffles in central and southern Europe, respectively. The cultivation potential of these high-prized cash crops under future warming, however, remains highly uncertain. Here we perform a literature review to define the ecological requirements for the growth of both truffle species. This information is used to develop niche models, and to estimate their cultivation potential in the Czech Republic under current (2020) and future (2050) climate conditions. The Burgundy truffle is already highly suitable for cultivation on ~ 14% of agricultural land in the Czech Republic (8486 km2), whereas only ~ 8% of the warmest part of southern Moravia are currently characterised by a low suitability for Périgord truffles (6418 km2). Though rising temperatures under RCP8.5 will reduce the highly suitable cultivation areas by 7%, the 250 km2 (3%) expansion under low-emission scenarios will stimulate Burgundy truffles to benefit from future warming. Doubling the moderate and expanding the highly suitable land by 352 km2 in 2050, the overall cultivation potential for Périgord truffles will rise substantially. Our findings suggest that Burgundy and Périgord truffles could become important high-value crops for many regions in central Europe with alkaline soils. Although associated with uncertainty, long-term investments in truffle cultivation could generate a wide range of ecological and economic benefits.